Teacher Experiences in the Universal Learning Design Framework - Widya Trio Pangestu; Humairah Fauziah; Yohannes Kurniawan Barus (Universitas Pendidikan Ganesha, 2025)
With the increasing importance of technology in education, understanding its potential for outdoor learning is crucial. Based on this, the purpose of this study was to analyze teachers' experiences in implementing the Universal Design for Learning (UDL) framework in the classroom. This study employed a qualitative descriptive research design. The study gathered insights from 13 elementary school teachers. The primary data collection method used was in-depth semi-structured interviews. The data analysis technique employed descriptive qualitative analysis. The study's main findings indicate that teachers' experiences in implementing Universal Design for Learning (UDL) significantly contribute to creating a more inclusive and responsive learning environment for learner diversity. Teachers can utilize various differentiation strategies, including the use of varied media, flexibility in delivery methods, and adaptive assessments tailored to individual student needs. However, the study also found that teachers still face challenges, particularly related to limited resources and time, as well as a lack of understanding of UDL principles. The implications of this study emphasize that the application of Universal Design for Learning (UDL) should serve as a basis for developing inclusive education policies and practices at various levels. Findings on teachers' experiences indicate that adequate support, whether in the form of training, provision of resources, or professional mentoring, is crucial for strengthening teachers' ability to adapt learning to the needs of diverse learners.